PEMAHAMAN KEAGAMAAN SALAFI DAN KEGADUHAN DI TENGAH MASYARAKAT SERTA SOLUSI PENYELESAIANNYA - Zikriadi Zikriadi; Muhammad Amri; Indo Santalia (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2022)
This study discusses the understanding of salafi religion in the community which always creates noise in the community. This research is included in the literature review with the stages of analysis in the form of data reduction, data exposure, and conclusions/verification. The results show that the Salafi understanding tends to be textual in understanding the Qur'an and Hadith, from this habit it has an impact on an understanding that traditions that live in a good society, which have never existed in the Qur'an and Hadith are always considered as a wrong understanding (bid'ah and shirk), even contrary to the teachings of Islam. One solution that must be done so that salafi understanding does not develop by paying special attention to the ustadz concerned to stop understanding that does not lead to noise, for example by giving priority to religious instructors from the Ministry of Religion to conduct a data collection program for clerics who tend to make noise and provide understanding. considered good for the sake of maintaining peace and religious tolerance